Genetic diversity in cocoa (Theobroma cacao L.) germplasm collection from Ghana - Opoku, S.; Bhattacharjee, Ranjana; Kolesnikova-Allen, M.; Motamayor, J.; Schnell, R.; Ingelbrecht, I.L.; Enu-Kwesi, L.; Adu-Ampomah, Y. (Informa UK Limited, 2007)
Theobroma cacao L. with its center of diversity in Central and South America was first introduced to West Africa in the mid-19th century and today the region produces 70% of the world's cocoa. Several distinct cocoa types have been introduced, cultivated, and intercrossed across the region. Also, bi-parental crosses involving selections from various introductions have been planted on a large scale. Consequently, a wide range of genetic diversity that could be exploited for crop improvement is expected. The present study has been, therefore, undertaken to assess the degree and distribution of genetic diversity present in cocoa germplasm collections from the Cocoa Research Institute (CRIG), seed gardens and materials from farmers' plantations in Ghana, using molecular markers. Two hundred and thirty-five trees representing all the cocoa-growing regions of Ghana were sampled in situ from farmers' fields and grouped as farmers' collection. Another set of 104 trees was collected from breeders' seed gardens, called breeders' collection. Thirty-eight parental clones from the CRIG's collection, used in producing the bi-parental crosses, comprised the third category, called parental clones. The collections were screened with the set of 17 mapped microsatellite markers. Average gene diversity was high in all populations, with mean observed heterozygosity of 0.738. Although the highest was recorded in accessions from breeders' and parental collections, genetic diversity in the farmers' collection was comparable with them. Despite the low level of differentiation [Fst = 0.076] found across all the three groups, sufficient genetic differences existed between them, separating breeders' collection from farmers' collection. The study also revealed the pattern of adoption of available planting materials by farmers on their fields.